Image of sport tourism Kiara Artha Park Bandung - Hidayat, Dasrun; Gustini, Leili Kurnia; Christin, Maylanny; Nur’aeni, Nur’aeni; Taufik, Reza Rizkina (PRofesi Humas, 2023)
Background: Sports tourism is a new approach to growing public interest in sports. Sports tourism is expected to foster interest in sports and build an image of sport tourism as a dual force that can help economic growth. Purpose: The research was conducted at Kiara Artha Park, one of the sports tourism sites in Bandung. The aim is to analyze the stages of forming the image of Kiara Artha sports tourism. Methods: Using a qualitative and phenomenology approach, involving 11 informants: Kiara Artha Park managers, tenants, and visitors. Results: The study results explain that the image built in Kiara Arta Park is a place of recreation with the concept of healthy living. The stages of building the image of Kiara Artha Park begin with the commitment of the management to prepare facilities in the form of green open land designed as a recreational park and exercise. They are also conducting socialization in conventional media, building sports community support, and managing community participation of social media users. Conclusion: The image of Kiara Artha Park as a tourist sport place is built through public awareness as users need a place to exercise and recreation. The two combined concepts encourage interest in maintaining a healthy life. Thus, the type of image formed is a user image or image built by consumers based on personal needs related to personality, lifestyle, and social status. Implications: The results of this study can provide input to the management and government of the city of Bandung as a policy in every tourist destination to provide sport tourism facilities as an additional public space that can improve the physical and mental health of the community.